2004
DOI: 10.1351/pac200476030465
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed asymmetric addition of aryl- and alkenylboron reagents to electron-deficient olefins

Abstract: Asymmetric 1,4-arylation and -alkenylation was achieved by use of organoboronic acids or their derivatives in the presence of a rhodium catalyst coordinated with binap or its related ligands. The scope of this asymmetric addition is very broad, α,β-unsaturated ketones, esters, amides, 1-alkenylphosphonates, and 1-nitroalkenes being efficiently converted into the corresponding 1,4-addition products with over 95 % enantioselectivity. The catalytic cycle in water is proposed to involve three intermediates [aryl-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The chapter is not intended to be comprehensive, and will include only selected examples of this powerful methodology. For more in-depth and comprehensive accounts, the reader should consult a number of excellent reviews that are available on this subject [6][7][8][9][10][11][12][13][14][15][16]. The first example of conjugate addition of an arylboronic acid to an enone catalyzed by transition metal complexes can be traced back to a report from 1995 by Uemura and coworkers [1].…”
Section: Introductionmentioning
confidence: 99%
“…The chapter is not intended to be comprehensive, and will include only selected examples of this powerful methodology. For more in-depth and comprehensive accounts, the reader should consult a number of excellent reviews that are available on this subject [6][7][8][9][10][11][12][13][14][15][16]. The first example of conjugate addition of an arylboronic acid to an enone catalyzed by transition metal complexes can be traced back to a report from 1995 by Uemura and coworkers [1].…”
Section: Introductionmentioning
confidence: 99%
“…These planar-chiral, mono-and di-phosphines have been employed as ligands in Rh-catalyzed 1,4-addition reactions to activated olefins, to afford the corresponding products 66a-j with up to 97 and 93% ee, respectively (Schemes 26 and 27). 89 This is the first example of the application of a planar chiral nonmetallocene ligand in the Rh-catalyzed 1,4-addition of arylboronic acids 66a-j to enones and enoates 1a resulting in high ee (>90%). It was found that cyrhetrene L14a, which is the easiest to purify and handle, is the most active in both catalytic reactions, furnishing the products with up to 97 and 93% ee.…”
Section: Methodsmentioning
confidence: 92%
“…For evaluating the scope of the catalyst system, different arylboronic acids 2 bearing electron-withdrawing as well as electron-donating groups using cyrhetrene L14a, L14b as the ligand were examined (Table 14). 89 Scheme 21. The reactions of other acyclic and cyclic enones 1a-c,1e,1g with phenylboronic acid 2 were also examined (Table 15).…”
Section: Methodsmentioning
confidence: 99%
“…2c, 2i, 9 In contrast to aryl boronic acids, alkenyl boronic acids are less stable. 10 Moreover, the reactions with boronic acids are carried out in solvent 65 mixtures containing water and therefore synthetically valuable rhodium-enolate intermediates cannot be trapped and used for further chemical transformations.…”
Section: Rhodium-catalyzed Aca Reactionsmentioning
confidence: 99%